Disruptive innovation factors influencing financial service performance: An in-depth analysis at the Mohammad Bin Rashid Centre for Government Innovation, Dubai, UAE - Almansoori, Khalifa (2024)
The concept of disruptive innovation, characterised by the introduction of novel products or services that fundamentally alter the market landscape, has become increasingly pivotal in shaping the trajectories of economic sectors, mainly financial services performance. This study delves into the impact of disruptive innovation on financial service performance, with a specific focus on the UAE, using the Mohammad Bin Rashid Centre for Government Innovation in Dubai as a case study. By synthesising the Innovation Diffusion Theory and the Technology Acceptance Model, this research constructs a conceptual framework to explore how disruptive innovation factors, mediated by disruptive business models and moderated by disruptive technologies, influence financial service performance. Employing a quantitative methodology, data were gathered from 315 executive banking officers through structured questionnaires and analysed using Structural Equation Modelling (SEM). The findings underscore the significant positive relationships between economic, environmental, and social factors of disruptive innovation and financial service performance. Furthermore, the study highlights the critical mediating role of disruptive business models and the moderating influence of disruptive technology in this dynamic. Theoretically, this research enriches the discourse on disruptive innovation by integrating the Innovation Diffusion Theory and the Technology Acceptance Model to offer a nuanced understanding of the mechanisms through which disruptive innovation factors affect financial service performance. It advances a holistic view of talent management (TM) by transcending the traditional binary of inclusive versus exclusive approaches, advocating for a synergistic integration of TM mindset and TM strategies. This approach provides a fresh perspective on the interplay between disruptive innovation and financial service performance, underpinned by the principles of Social Exchange Theory (SET), which elucidates the mediating effects of job engagement and satisfaction in the TM-performance nexus. Practically, the insights gleaned from this study are poised to inform policy formulation and strategic decision-making in the UAE. By delineating the pathways through which disruptive technologies and business models can bolster financial service performance, the findings offer actionable intelligence for policymakers aiming to foster an innovation- driven economic environment and for managers seeking to harness disruptive innovations to enhance competitiveness and efficiency in the financial sector. In sum, this study contributes to the theoretical enrichment of disruptive innovation literature and provides a pragmatic blueprint for leveraging disruptive technologies and business models to propel the growth and dynamism of financial services in the UAE.